Photodynamic therapy promotes hypoxia‐activated nitrogen mustard drug release - Ran Wang; Maomao He; Zongwei Zhang; Tian Qiu; Yue Xi; Xiaolong Zeng; Jiangli Fan; Wen Sun; Xiaojun Peng (Smart Molecules, 2024)
Abstract Photodynamic therapy (PDT) has become a promising method for tumor treatment due to its non‐invasive and high spatiotemporal selectivity. However, PDT is still hindered by reactive oxygen species deficiency, because solid tumors feature a hypoxic microenvironment. PDT combined with hypoxia‐activated chemotherapy drugs can effectively induce tumor death, overcoming the limitations of the sole PDT for the fight against hypoxia. Herein, we designed a nanosystem (PCe6AZOM) that enhances the release of hypoxia‐activated drugs (AZOM) by PDT. Under hypoxic conditions, the azo bond of AZOM is cleaved by azo reductase, releasing highly cytotoxic AZOM and resulting in a significant increase in intratumor drug concentration. Meanwhile, the commercial photosensitizer Ce6 can aggravate the oxygen‐poor state during the PDT process and further cause more AZOM release. Moreover, the cascade reactions in the nanosystem could activate singlet oxygen and enhance drug release through 660 nm light laser irradiation, contributing to more effective induction of tumor apoptosis and tumor growth retardation in vitro and in vivo.